2020
DOI: 10.5194/acp-2020-1041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidation of low-molecular weight organic compounds in cloud droplets: global impact on tropospheric oxidants

Abstract: Abstract. In liquid cloud droplets, superoxide anion (O−2(aq)) is known to quickly consume ozone (O3(aq)), which is relatively insoluble. The significance of this reaction as tropospheric O3 sink is sensitive to the abundance of O−2(aq) and therefore to the production of its main precursor, hydroperoxyl radical (HO2(aq)). The aqueous-phase oxidation of oxygenated volatile organic compounds (OVOCs) is the major source of HO2(aq) in cloud droplets. Hence, the lack of explicit aqueous-phase chemical kinetics in g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Similar to the HOOVER campaigns, NO, O 3 and CO can be well approximated by the model simulations which we present in Figure S2 and S3 of the Supplement. Tropospheric ozone is slightly overestimated, which we attribute to the simplified representation of multiphase chemistry (clouds) in the present model version, which underpredicts chemical ozone loss (Rosanka et al, 2021).…”
Section: Comparison Of Model and Experimentsmentioning
confidence: 72%
“…Similar to the HOOVER campaigns, NO, O 3 and CO can be well approximated by the model simulations which we present in Figure S2 and S3 of the Supplement. Tropospheric ozone is slightly overestimated, which we attribute to the simplified representation of multiphase chemistry (clouds) in the present model version, which underpredicts chemical ozone loss (Rosanka et al, 2021).…”
Section: Comparison Of Model and Experimentsmentioning
confidence: 72%
“…SCAV calculates the transfer of species into and out of rain and cloud droplets using the Henry's law equilibrium, acid dissociation equilibria, oxidation-reduction reactions, heterogeneous reactions on droplet surfaces, and aqueous-phase photolysis reactions (Tost et al, 2006). As mentioned earlier and as demonstrated by Rosanka et al (2020b), in-cloud OVOC oxidation significantly influences the atmospheric composition. However, the ordinary differential equations (ODE) systems resulting from the combination of gas-phase and in-cloud aqueous-phase suffer from (1) a higher stiffness due to fast acid-base equilibria and phase-transfer reactions, and (2) load imbalance on High-Performance Computing (HPC) systems due to the sparsity of clouds.…”
Section: Atmospheric Chemistrymentioning
confidence: 97%
“…Many oxygenated VOCs (OVOCs) have a high solubility and quickly partition and react in cloud droplets influencing radical concentrations and the atmospheric composition in general (Herrmann et al, 2015). Rosanka et al (2020b) showed that the in-cloud OVOC oxidation has a significant impact on the predicted concentrations of VOCs, key oxidants, and O 3 .…”
Section: Introductionmentioning
confidence: 99%